Keto diet - Abrams, Rami; Abrams, Vicky (--For dummies., 2026)
"Keto Diet For Dummies is your updated guide to the low-carb, high-fat ketogenic diet. It's a great time to try this healthful approach, thanks to new research, new recipes, and new keto products on the market. In this book, you'll find easily digestible info on how the keto diet trains your body to rely on fat as its energy source, for weight loss, reduced inflammation, improved mental health, and a host of other benefits. Then, the expert authors help you create the perfect keto plan to be the healthiest version of yourself. You'll even learn how to use AI to help you plan and prep great keto meals. What a time to be alive!"